Classical sociology beyond methodological nationalism - Pendenza, Massimo (International studies in sociology and social anthropology, 2014)
Classical Sociology Beyond Methodological Nationalism defends classical sociology from the accusation of 'methodological nationalism' and re-evaluates classical sociological thought as a more functional tool for analysing the political forms of modernity in the era of globalisation.